Seroprevalence of Coxiella burnetii and potential tick vectors infesting domestic ruminants and community perception of the disease in pastoral areas of south Omo zone, southern Ethiopia - Senait Getachew; Bersissa Kumsa; Yitbarek Getachew; Getachew Kinfe; Balako Gumi; Tesfaye Rufael; Bekele Megersa (Parasite Epidemiology and Control, 2024)
Background: Q fever is a worldwide occurring neglected zoonotic disease with great economic importance. The etiological agent, Coxiella burnetii, is a bacterium usually associated with subclinical infections in livestock, but may also cause reproductive pathology and spontaneous abortions in artiodactyl species including goats, sheep and cattle which are deemed to be the primary reservoirs of this disease. Aims: The present cross-sectional and questionnaire survey was undertaken in three districts of the South Omo zone with the aims to comprehend the community perception of livestock keepers and professionals about the disease, estimate the seroprevalence of Coxiella burnetii (C. burnetii) in cattle and small ruminants and to determine the species of potential tick vectors of C. burnetii infesting cattle, sheep and goats. Methods: A standard questionnaire was used to assess the community perception of livestock keepers and animal health professionals in the area about Q fever. Sera samples were collected from 1350 ruminants comprising 450 cattle, 450 goats and 450 sheep to detect C. burnetii antibodies using the ELISA technique. Furthermore, a total of 279 cattle, 197 goats and 73 sheep were examined for the presence of ticks, and overall, 2720 ticks were collected (1299 from cattle, 1020 from goats and 401 from sheep) and identified to the species level using morphologically identification keys. Results: Findings of the study indicated that 43% of animal owners were aware of the main symptoms of the disease while the remaining 57% did not notice these symptoms in their animals. Additionally, majority of animal health professionals 76.2% in the area reported they were familiar with the causative agent of Q fever, while 23.8% expressed uncertainty regarding the cause of coxiellosis. An overall seroprevalence of C. burnetii of 37.6% in cattle (37.4% in female and 37.8% in male cattle) and 28.7% in small ruminants was recorded (which is significantly higher in goats than in sheep). The study indicated statistically significantly higher seroprevalence of C. burnetii (49.8%) in cattle infested with ticks than in those cattle free of ticks (24.2%), with three times higher seropositivity (OR = 2.97, p = 0.000) as compared to those cattle free of ticks (24.2%). Similarly, statistically significantly higher seroprevalence of C. burnetii was recorded in both sheep and goats infested with ticks (43.6%) as compared to those animals without ticks (22.9%), with the former being twice as likely to test seropositive (OR = 2.15, p = 0.000). A total of nine different tick species were identified, namely Amblyomma variegatum (Am. variegatum) with 26.3% (342; 217 males, 101 females and 24 nymphs), Amblyomma cohaerens (Am. cohaerens) with 47.96% (370 males, 253 females), Amblyomma gemma (Am. gemma) with 4.00% (52; 29 males, 23 female), Rhipicephalus pulchellus (Rh. pulchellus) with 10.6% (138; 87 males, 51 females), Rhipicephalus pravus (Rh. pravus) with 0.2% (3; 2 males, 1 females), Rhipicephalus evertsi (Rh. evertsi) with 4.7% (61; 39 males, 22 females), Rhipicephalus praetextatus (Rh. praetextatus) with 0.8% (10; 7 males, 3 females), Rhipicephalus decoloratus (Rh decoloratus) with 2.9% (38; 4 males, 34 females) and Hyalomma truncatum (Hy. truncatum) with 2.5% (32 females). Conclusion: The present study highlighted the significance of Q fever in ruminants and compiled information about the community perception of livestock keepers and veterinary professionals of the study areas. The role of ruminants and their ticks in the epidemiology of C. burnetii requires further research using molecular tools to better understand appropriate method of intervention that will help to reduce negative impacts on the productivities of livestock and the health of humans in Ethiopia.